Pertumbuhan Konsorsium Mikroalga Dalam Palm Oil Mill Effluent (POME) Dengan Sistem Kultur Semikontinu - Novira, Tria Bela; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The growing palm oil industry in Indonesia is causing an increase in Palm Oil Mill Effluent (POME) generated. The organic material contained in POME can be a nutrient source for microalgae growth. The growth of the microalgae consortium will increase after the replacement as an addition of nutrients to the culture medium. The aim of this research to determine the growth rate microalgae consortium in POME as a culture medium. The research was conducted in semicontinuous system by replacing half volume of culture with fresh POME in period every 3 days, 4 days, and 6 days for 12 days of cultivation. The result showed the best cultivation conditions was every 6 days replacement period which spesific growth rate 0,212/day on the 12th day. Keywords: Microalgae consortium, Palm Oil Mill Effluent (POME), Replacement period